PURCHASE INTENTION ON HALAL CULINARY FAST FOOOD IN YOGYAKARTA - Nafisah Arinilhaq (Universitas Muhammadiyah Yogyakarta, 2017)
The purpose of this research is to identify and determine the influence of halal factors on Purchase Intention through Subjective Norms. It also investigated which one factor among all variables that are investigated have the strongest influence. The study was taken from 139 respondents of Muslim consumers of halal culinary fast food, KFC. The collected data is measured by five-point Likert scale. Used Structural Equation Model (SEM) with IBM AMOS version 24 as analytical tool, this research was divided into 5 variables which are measured. The variables are Halal Awareness, Halal Certification, Halal Marketing Word of Mouth (WOM), Subjective Norms and Purchase Intention. The measurement is based on Theory Planned of Behavior by Ajzen (1991) with modification. Result shows that Subjective Norms has high connection with Purchase Intention. It caused by indirect effect from Halal Certification and Halal Marketing WOM. But direct effect from Halal Awareness and Halal Marketing WOM is not significant. Thereby, the study suggests that customers are influenced by Subjective Norms or Muslim consumers’ preference as they are being influenced by halal label or Halal Certification and also word of mouth marketing system. The study suggests KFC or food manufactures have to pay attention to halal marketing strategy. Based from the finding, it can be concluded that, consumer did not look for about halal by themselves, but pay attention to the halal label and WOM marketing strategy.